2013
DOI: 10.1007/s13142-013-0206-3
|View full text |Cite
|
Sign up to set email alerts
|

Mobile apps for pediatric obesity prevention and treatment, healthy eating, and physical activity promotion: just fun and games?

Abstract: Mobile applications (apps) offer a novel way to engage children in behavior change, but little is known about content of commercially available apps for this population. We analyzed the content of apps for iPhone/iPad for pediatric weight loss, healthy eating (HE), and physical activity (PA). Fifty-seven apps were downloaded and tested by two independent raters. Apps were coded for: inclusion of the Expert Committee for Pediatric Obesity Prevention's (ECPOP) eight recommended strategies (e.g., set goals) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
134
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(140 citation statements)
references
References 14 publications
3
134
0
3
Order By: Relevance
“…To the authors' knowledge, no previous study has used smartphone technology in a school-based obesity prevention program 14 and few existing smartphone "apps" include evidence-based behavior change techniques. 19 Therefore, the primary aim of the present study was to evaluate the effects of the multicomponent, school-based obesity prevention intervention incorporating smartphone technology, known as ATLAS (Active Teen Leaders Avoiding Screen-time). This article reports the 8-month (immediate postprogram) intervention effects.…”
Section: Resultsmentioning
confidence: 99%
“…To the authors' knowledge, no previous study has used smartphone technology in a school-based obesity prevention program 14 and few existing smartphone "apps" include evidence-based behavior change techniques. 19 Therefore, the primary aim of the present study was to evaluate the effects of the multicomponent, school-based obesity prevention intervention incorporating smartphone technology, known as ATLAS (Active Teen Leaders Avoiding Screen-time). This article reports the 8-month (immediate postprogram) intervention effects.…”
Section: Resultsmentioning
confidence: 99%
“…Both show that the use of evidence-based behavioral strategies in apps is very low relative to the strategies typically employed in traditionally delivered interventions. Schoffman and colleagues found that 61 % of mobile apps targeting childhood obesity did not include any evidence-based behavioral strategies [6]. Breland and colleagues found that 14 % of diabetes mobile apps did not include any evidencebased behavioral strategies and 33 % included only one of six possible strategies [7].…”
Section: Do Mhealth Apps Work?mentioning
confidence: 99%
“…These findings are similar to findings from other reviews suggesting that few evidence-based techniques are included in the most popular weight loss apps for adults 11,[13][14][15] and in HE and PA apps for children. 12 Findings from this and other studies highlight the continued need for inclusion of more evidence-based techniques promoting HE behavior, including self-regulation, in an effort to better ensure the efficacy of these types of mobile apps for weight loss and reduction of chronic disease.…”
Section: Discussionmentioning
confidence: 77%
“…9 While mobile apps for weight loss are prevalent, most do not include evidencebased strategies and there is poor integration of these apps in weight loss interventions. [10][11][12][13][14][15] Adherence to diet self-monitoring is a key component of weight loss. 16,17 Previous studies have demonstrated that frequency of self-monitoring is significantly associated with weight loss 6,16 and that frequency of and adherence to self-monitoring is more important for weight loss than accuracy of nutritional data tracked.…”
mentioning
confidence: 99%